Social Cognition Individualized Activities Lab for Social Cognition Training and Narrative Enhancement in Patients With Schizophrenia: A Randomized Controlled Study to Assess Efficacy and Generalization to Real-Life Functioning (Prot. n°: NCT05130853) - Palumbo, Davide; Caporusso, Edoardo; Piegari, Giuseppe; Mencacci, Claudio; Torriero, Sara; Giuliani, Luigi; Fabrazzo, Michele; Pinto, Dario; Galderisi, Silvana (Frontiers in Psychiatry, 2022)
Subjects affected by schizophrenia present significant deficits in various aspects of social cognition, such as emotion processing, social perception and theory of mind. These deficits have a greater impact than symptoms on occupational and social functioning. Therefore, social cognition represents an important therapeutic target in people with schizophrenia. Recent meta-analyses showed that social cognition training (SCT) is effective in improving social cognition in subjects with schizophrenia; however, real-life functioning is not always ameliorated. Integration of SCT with an intervention targeting metacognitive abilities might improve the integration of social cognitive skills to daily life functioning. Our research group has implemented a new individualized rehabilitation programme: the Social Cognition Individualized Activities Lab, SoCIAL, which integrates SCT with a module for narrative enhancement, an intervention targeting metacognitive abilities. The present multi-centre randomized controlled study will compare the efficacy of SoCIAL and treatment as usual (TAU) in subjects diagnosed with a schizophrenia-spectrum disorder. The primary outcome will be the improvement of social cognition and real-life functioning; while the secondary outcome will be the improvement of symptoms, functional capacity and neurocognition. The results of this study will add empirical evidence to the benefits and feasibility of SCT and narrative enhancement in people with schizophrenia-spectrum disorders. Prot. n°: NCT05130853 https://clinicaltrials.gov/ct2/show/NCT05130853?term=NCT05130853&draw=2&rank=1